PENGEMBANGAN INSTRUMEN PEMAHAMAN KONSEP BERBASIS KOMPUTER PADA PEMBELAJARAN KIMIA - Muhammad Shohibul Ihsan; Saprizal Hadisaputra; Agus Ramdani; Agil Al Idrus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
This study aims to create a valid computer-based concept understanding instrumen as a measurement tool for students' understanding of chemistry subjects with basic ingredients of atomic structure. Research, including research and development (Research and Development) discusses the ADDIE development model, including Analysis, Design, Development, Implementation, Evaluation. Testing instrumens in learning is carried out on class X MIA MA Nahdlatul Wathan Mataram, NTB. Design research trials using One Group Pretest-Posttest Design. The results showed that the average value of the instrumen worthiness of the three validators was 82.2% with very reasonable criteria. The use of computer-based concept understanding instrumens in limited trials gained an average score of 80.5% from teachers and students with very practical criteria. The results of this study prove that the media developed have valid and practical concepts to increase students' understanding